Research on Annual Performance Factor of Water-water Heat Pump System - 杨昭; 赵海波; 胡云峰; 吴坤 (Zhileng xuebao)
The annual performance factor(APF) optimization of water-water heat pump was presented.Based on the building load in a whole year,the APF of a heat pump was defined and used as the optimization function,with the area ratio of heat exchanger as the optimization variable.The optimization mathematical models for the on-off control scheme were set up to calculate the APF to study the optimal design and matching between different components.Comparison with different optimization designs with HSPF,SEER,and EER,the APF optimization is nearer to the reality.